A profissionalidade docente: vivências de professores do Instituto Federal do Acre - Campus Xapuri - Silva, Deimisson Gomes da (Universidade Federal de São Carlos, 2024)
The present study aimed to investigate how teachers at the Federal Institute of Acre - Xapuri Campus understand teaching professionalism. The specific objectives were: to understand teachers' comprehension of teaching at the Federal Institute, its characteristics, and challenges; as well as teachers' experiences regarding professionalism, considering their statements about the profession. The research was based on Cultural-Historical Theory, focusing on Vygotsky's concept of "vivencia" (lived experience), and interviews were conducted with four teachers. The data indicated that teaching professionalism was related to various dimensions, such as: effectiveness of practice; social activism and transformation of subjects' reality; professional fulfillment; a more humanistic perspective and commitment to the scientific view of the world. Teaching at IF Xapuri Campus involved aspects such as: bureaucracy; excessive workload; education precarization; class relations; internalization process; and relationship with the local community, humanized and welcoming environment, as well as a sense of belonging to the context. The experiences highlighted by the teachers encompassed: sensitivity in work relationships and aesthetic experience of the world, where being in the profession is as important as doing. It is observed that teaching professionalism is seen as strongly marked by a sense of social responsibility towards students and the community, in providing them with the necessary conditions to develop as individuals and as professionals committed to transforming themselves and their environment. The studies have also pointed out that teaching professionalism involves subjective and objective issues, such as personal experiences and motivations, ways of acting, and working environment conditions, changing along with society as it is a social construction.
Teaching professionalism: experiences of teachers at the Federal Institute of Acre - Campus Xapuri
Keywords: Vivências; Profissionalidade docente; Institutos federais; Educação profissional e tecnológica; Experiences; Teaching professionality; Federal institutes; Professional and technological education; CIENCIAS HUMANAS; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO